Non-aqueous electrolyte and lithium ion battery thereof

By using Compound A of Structure Formula I and Compound B of Structure Formula II in lithium-ion batteries, the problems of electrolyte polarization and unstable positive electrode material during fast charging are solved, and the high-temperature fast charging cycle performance and high-temperature storage performance of the battery are significantly improved.

CN119812478AActive Publication Date: 2025-04-11HEFEI SMOOTHWAY ELECTRONIC MATERIALS CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510177021.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-04-11
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

During the fast charging process, existing lithium-ion batteries have problems such as intensifying electrolyte polarization, increasing internal resistance, unstable structure of the positive electrode material, and catalytic electrolyte decomposition of dissolved transition metal ions, which is difficult to meet the needs of fast charging and high-temperature storage performance.

Method used

A non-aqueous electrolyte is used, including Compound A of Structural Formula I and Compound B of Structural Formula II. Compound A can neutralize the alkalinity of the particles of the positive electrode active material, inhibit the solvent reaction in the electrolyte, and reduce the oxygen precipitation of the positive electrode; Compound B is a zwitterionic compound that can accelerate the dissociation of lithium salts and acid ions, improve the ionic conductivity of the electrolyte, and generate stable S-Li bonds through S-N bonds, enhancing the stability of the SEI film.

Benefits of technology

Through synergistic action, Compound A and Compound B significantly improve the high-temperature fast charging cycle performance and high-temperature storage performance of lithium-ion batteries, reduce the polarization internal resistance under fast charging conditions, and enhance the overall electrical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812478A_ABST
    Figure CN119812478A_ABST
Patent Text Reader

Abstract

The invention provides a non-aqueous electrolyte and a lithium ion battery thereof. The non-aqueous electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, the additive comprises a compound A shown as a structural formula I and a compound B shown as a structural formula II, R1 is selected from halogen or alkyl phenyl, R2 is selected from halogen or alkyl phenyl, and R3 is selected from halogen or alkyl phenyl. R2, R3, R4, R5 and R6 are independently selected from hydrogen, halogen, a cyano group, a substituted or unsubstituted alkyl group, a substituted or unsubstituted alkenyl group, a substituted or unsubstituted alkynyl group, a substituted or unsubstituted alkoxy group and a substituted or unsubstituted sulfonyl group. The non-aqueous electrolyte simultaneously contains the compound A shown in the structural formula I and the compound B shown in the structural formula II, and through the synergistic effect of the two substances, the high-temperature storage performance and the high-temperature fast charge cycle performance of the lithium ion battery can be improved. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a non-aqueous electrolyte and a lithium ion battery thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and large energy storage systems due to their high energy density, long cycle life and wide operating temperature range. With the advancement of technology, people's requirements for the performance of lithium-ion batteries are constantly increasing, especially the demand for fast charging performance is becoming more urgent. Fast charging performance often requires the electrolyte to have high ionic conductivity and fast lithium ion desolvation.

[0003] During the charge and discharge process of lithium cobalt oxide batteries, the lithium ions in the positive electrode are deintercalated and intercalated in the oxygen-cobalt oxygen layer, and reach the negative electrode through the electrolyte and the separator. During fast charging, the battery is under high current density, which will cause the electrolyte polarization in the battery to increase and the internal resistance to increase, which requires the ions in the electrolyte to move fast enough. At the same time, the fast charging process of lithium batteries is often accompanied by problems such as unstable positive electrode material structure, even structural collapse and destruction, and dissolution of transition metal ions catalyzing the decomposition of the electrolyte.

[0004] Therefore, it is urgent to develop a non-aqueous electrolyte suitable for lithium cobalt oxide batteries to address the shortcomings of the existing technology. Summary of the invention

[0005] The object of the present invention is to provide a non-aqueous electrolyte and a lithium ion battery thereof, wherein the non-aqueous electrolyte contains both compound A shown in structural formula I and compound B shown in structural formula II. Through the synergistic effect of these two substances, the high-temperature fast charging cycle performance and high-temperature storage performance of the lithium ion battery can be improved.

[0006] To achieve the above object, the present invention provides a non-aqueous electrolyte, including a lithium salt, a non-aqueous organic solvent and an additive, wherein the additive includes a compound A shown in structural formula I:

[0007] And, compound B shown in structural formula II:

[0008] Wherein, R1 is selected from halogen or alkylphenyl, and R2, R3, R4, R5, and R6 are each independently selected from hydrogen, halogen, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted alkoxy, or substituted or unsubstituted sulfonyl.

[0009] Compared with the prior art, the non-aqueous electrolyte of the present invention includes a lithium salt, a non-aqueous organic solvent and an additive. The compound shown in structural formula I can neutralize the alkalinity of the surface of the positive electrode active material particles on the surface of the positive electrode plate, inhibit the reaction of the solvent in the electrolyte on the surface of the positive electrode plate, and the compound shown in structural formula I contains selenium, which can lose electrons preferentially compared to the oxygen of the positive electrode, thereby reducing the generation of singlet oxygen at the positive electrode, thereby reducing the oxidation of the electrolyte by singlet oxygen. The compound shown in structural formula II is a zwitterionic compound. The additive interacts with the lithium salt in the electrolyte, accelerates the dissociation of the lithium salt and the acid radical ion, thereby improving the ionic conductivity of the electrolyte, accelerating the transmission speed of lithium ions, greatly reducing the polarization internal resistance under fast charging conditions, thereby improving the fast charging performance; and due to the instability of the SN bond in the additive structure, it can generate a stable S-Li bond in situ when forming the CEI film, increasing the stability of the CEI film and improving the electrical performance of the battery under high temperature conditions. In addition, the two nitrogen atoms in the additive structure have a certain degree of complexation with the metal ions in the positive electrode material, making the structure of the positive electrode material more stable. Under overall conditions, the combination of the two additives combines the advantages of the two additives, thereby improving the high-temperature fast-charge cycle performance and high-temperature storage performance of lithium-ion batteries. Further, R1 is selected from halogen or methylphenyl, and R2, R3, R4, R5, and R6 are each independently selected from hydrogen, halogen, cyano, substituted or unsubstituted C1~C10 alkyl, substituted or unsubstituted C2~C10 alkenyl, substituted or unsubstituted C2~C10 alkynyl, substituted or unsubstituted C1~C10 alkoxy, and substituted or unsubstituted C1~C10 sulfonyl.

[0010] Further, R1 is selected from fluorine, chlorine or p-methylphenyl, R2, R3, R4, and R5 are each independently selected from hydrogen or halogen, and R6 is selected from hydrogen, halogen, cyano, substituted or unsubstituted C1~C6 alkyl, substituted or unsubstituted C2~C6 alkenyl, substituted or unsubstituted C2~C6 alkynyl, substituted or unsubstituted C1~C6 alkoxy, substituted or unsubstituted C1~C6 sulfonyl, and when substituted, the substituent is selected from at least one of halogen or cyano.

[0011] Furthermore, the compound B of the present invention is selected from at least one of compounds 1 to 11:

[0012]

[0013] Specifically, compound 1 can be prepared according to the following synthetic route:

[0014] The synthetic routes of compounds 2 to 9 can refer to compound 1, except that the compound with Cas number 110-86-1 in the synthetic route of compound 1 is replaced by the following compounds:

[0015]

[0016] Compound 10 can be prepared according to the following synthetic route:

[0017] Compound 11 can be prepared according to the following synthetic route:

[0018] Further, the mass percentage of compound A of the present invention in the non-aqueous electrolyte is 0.05-5%, and the mass percentage of compound B in the non-aqueous electrolyte is 0.05-5%. As an example, the mass percentage of compound A in the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%. The mass percentage of compound B in the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%.

[0019] Furthermore, the mass percentage of compound A in the non-aqueous electrolyte is 0.1-2%, and the mass percentage of compound B in the non-aqueous electrolyte is 0.1-4%.

[0020] Furthermore, the mass percentage of compound A in the present invention in the non-aqueous electrolyte is 0.1-1%, and the mass percentage of compound B in the non-aqueous electrolyte is 0.1-2%.

[0021] Further, the lithium salt of the present invention is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethylsulfonate (LiCF3SO3), lithium bistrifluoromethylsulfonyl imide (LiN(CF3SO2)2), lithium bis(oxalatoborate) (C4BLiO8), lithium difluorophosphate (LiPO2F2), lithium fluorosulfonate, lithium difluorooxalatoborate (LiODFB), lower aliphatic lithium carboxylates, lithium difluorobis(oxalatophosphate) (LiDODFP) and lithium bis(fluorosulfonyl imide) (LiFSI). Lower aliphatic lithium carboxylates include but are not limited to lithium chloroborane, lithium tetraphenylborate, lithium imide salts, and the like. As an example, the lithium salt is lithium hexafluorophosphate (LiPF6), but is not limited thereto. Further, the lithium salt is a mixture of lithium hexafluorophosphate and lithium bis(oxalatoborate), but is not limited thereto.

[0022] Further, the mass percentage of the lithium salt of the present invention in the non-aqueous electrolyte is 5-25%, further, the mass percentage of the lithium salt in the non-aqueous electrolyte is 8-20%, more preferably, the mass percentage of the lithium salt in the non-aqueous electrolyte is 10-15%, as an example, the mass percentage of the lithium salt in the non-aqueous electrolyte may be but is not limited to 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 20%, 22%, 23%, 24%, 25%.

[0023] Furthermore, the non-aqueous organic solvent of the present invention is at least one selected from carboxylic acid esters, carbonates and ether compounds.

[0024] Specifically, the carboxylic acid ester includes but is not limited to at least one of γ-butyrolactone (γ-Bt), γ-valerolactone (GVL), δ-valerolactone (DVL), methyl acetate (MA), ethyl acetate (EA), ethyl propionate (EP), butyl acetate (n-Ba), propyl propionate (n-PP), and butyl propionate (PRB).

[0025] Specifically, the carbonate includes, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PCA), butylene carbonate (BC), pentylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl n-propyl carbonate, ethyl n-propyl carbonate, and propylene carbonate (PC).

[0026] Specifically, the ether compounds include, but are not limited to, at least one of 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ether, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH3-THF), 2-trifluoromethyltetrahydrofuran (2-CF3-THF), dimethoxymethane (DMM), diethoxymethane (DEM), ethoxymethoxymethane (DCE), ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether (EDB), and diethylene glycol dimethyl ether (DEGME).

[0027] Further, the mass percentage of the non-aqueous solvent in the non-aqueous electrolyte of the present invention is 65-90%, preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 75-89%, and more preferably, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte is 78-88%. As an example, the mass percentage of the non-aqueous organic solvent in the non-aqueous electrolyte may be, but is not limited to, 65%, 70%, 75%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 90%.

[0028] Furthermore, the non-aqueous electrolyte of the present invention also includes an auxiliary agent, which is selected from at least one of fluoroethylene carbonate (FEC), vinylene carbonate (VC), 1,3-propane sultone (PS), diethylene sulfate (DTD), 1,3-propylene glycol cyclosulfate (PCS), 1,4-butane sultone (1,4-BS), triallyl phosphate (TAP) and succinic anhydride (SA).

[0029] Furthermore, the mass percentage of the auxiliary agent of the present invention in the non-aqueous electrolyte is 0.1-5%. By way of example, the mass percentage of the auxiliary agent in the non-aqueous electrolyte may be, but is not limited to, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, and 5.0%.

[0030] Another aspect of the present invention provides a lithium-ion battery, comprising a positive electrode material and a negative electrode material, and also comprising the above-mentioned non-aqueous electrolyte.

[0031] Furthermore, the positive electrode material of the present invention is selected from lithium cobalt oxide, and its chemical formula is LiCoO2.

[0032] Further, the negative electrode material of the present invention is selected from at least one of artificial graphite, natural graphite, lithium titanate, silicon-carbon composite material and silicon oxide. As an example, the negative electrode material is artificial graphite, but it is not limited thereto. DETAILED DESCRIPTION

[0033] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0034] Example 1 (1) Preparation of non-aqueous electrolyte In a glove box filled with argon (O2 <1ppm, H2O <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) were mixed in a weight ratio of EC:EMC:DEC=1:1:1 to obtain 86.5g of a non-aqueous organic solvent, followed by adding 0.5g of compound A and 0.5g of compound 1 as additives, dissolving and stirring well, then adding 12.5g of lithium hexafluorophosphate, and mixing well to obtain a non-aqueous electrolyte.

[0035] (2) Preparation of positive electrode LiCoO2, adhesive PVDF and conductive agent SuperP are mixed evenly in a mass ratio of 95:1:4 to prepare a lithium-ion battery positive electrode slurry with a certain viscosity. The mixed slurry is coated on both sides of an aluminum foil, and then dried and rolled to obtain a positive electrode sheet.

[0036] (3) Preparation of negative electrode Artificial graphite, conductive agent SuperP, thickener CMC, and adhesive SBR (styrene-butadiene rubber latex) are made into slurry in a mass ratio of 95:1.5:1.0:2.5, mixed evenly, coated on both sides of copper foil with the mixed slurry, and then dried and rolled to obtain a negative electrode sheet.

[0037] (4) Preparation of lithium-ion batteries The positive electrode, the separator and the negative electrode are wound into a soft-pack battery cell, which is packaged with a polymer aluminum-plastic film and filled with the prepared lithium-ion battery non-aqueous electrolyte. After the processes of formation and capacity separation, a lithium-ion battery with a capacity of 4000 mAh is manufactured.

[0038] The non-aqueous electrolyte formulations of Examples 1-20 and Comparative Examples 1-3 are shown in Table 1, wherein the steps of preparing the non-aqueous electrolyte and preparing the lithium-ion batteries of Examples 2-20 and Comparative Examples 1-3 are the same as those of Example 1.

[0039] Table 1 Non-aqueous electrolyte formula of Examples 1 to 20 and Comparative Examples 1 to 3

[0040] The lithium ion batteries prepared in Examples 1 to 20 and Comparative Examples 1 to 3 were subjected to high temperature storage tests and high temperature fast charge cycle tests, respectively. The specific test conditions are as follows. The performance test results are shown in Table 2.

[0041] High temperature storage performance test At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C0), and the upper limit voltage is 4.53V; the battery is placed in a 60°C oven for 7 days, the battery is taken out, and the battery is placed in a 25°C environment for 0.3C discharge, and the discharge capacity is recorded as C1; then the lithium-ion battery is charged and discharged at 0.3C / 0.3C (the battery discharge capacity is recorded as C2), and the capacity retention rate and capacity recovery rate of the lithium-ion battery are calculated using the following formula:

[0042]

[0043] High temperature fast charging cycle performance test Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to make the lithium-ion battery reach a constant temperature. Charge it at a constant current of 2C to a voltage of 4.53V, then charge it at a constant voltage of 4.53V to a current of 0.05C, and then discharge it at a constant current of 1C to a voltage of 3.0V. Record the first discharge capacity of the battery as C0, which is a charge and discharge cycle. Then charge and discharge at 2C / 1C for 300 cycles at 45℃, record the discharge capacity as C1, and use the following formula to calculate the capacity retention rate of the lithium-ion battery.

[0044]

[0045] Table 2 Performance test results of Examples 1 to 20 and Comparative Examples 1 to 3

[0046] It can be seen from the results in Table 2 that, compared with Comparative Examples 1 to 3, the lithium-ion batteries of Examples 1 to 20 have good high-temperature storage performance and high-temperature fast-charge cycle performance at a high voltage of 4.53V. This may be because in the battery, compound B shown in structural formula II is a zwitterionic compound, and the additive structure contains a sulfonimide group and a pyridine ring. The negative charge is mainly concentrated on the nitrogen atom connected to the sulfur atom, while the positive charge is concentrated on the nitrogen atom on the pyridine ring. The sulfonimide group is connected to the pyridine ring through a carbonyl group, which makes the additive interact with the lithium salt in the electrolyte, accelerates the dissociation of the lithium salt and the acid radical ion, and thus improves the ionic conductivity of the electrolyte; and due to the instability of the SN bond in the additive structure, it can generate a stable S-Li bond in situ when forming the SEI film, which increases the stability of the SEI film; in addition, the two nitrogen atoms in the additive structure are very sensitive to the Li in the positive electrode material. + 、Co 3+ It has a certain degree of complexation, making the structure of lithium cobalt oxide more stable. At the same time, the compound shown in structural formula I can be adsorbed on cobalt ions on the surface of the positive electrode through cyano groups to inhibit the dissolution of cobalt. At the same time, when the positive electrode is deeply delithiated, its selenium atoms can provide electrons to reduce the precipitation of lattice oxygen as singlet oxygen, thereby reducing the oxidation of the electrolyte by singlet oxygen and reducing the catalytic decomposition of the electrolyte by cobalt dissolution. The simultaneous use of compound A shown in structural formula I and compound B shown in structural formula II can act synergistically, which can not only stabilize the positive electrode of the battery, improve the crushing and dissolution phenomenon on the surface of the positive electrode, but also form a stable CEI film, improve the conductivity of the electrolyte, and facilitate lithium ion migration, thereby improving the high temperature storage performance and high temperature fast charging cycle performance of the battery.

[0047] Further, by comparing Examples 1 to 11, it can be seen that by adjusting the substituents with different functions on the pyridine ring, the various properties of the lithium-ion battery will also be affected to varying degrees. More specifically, when Compound A is used in combination with Compound 9, the various properties of the lithium-ion battery are optimal, which may be because the fluorosulfonyl group introduced by Compound 9 is a strong electron-withdrawing group that can make the charge on the pyridine ring more dispersed, making the structure of the compound more stable. In addition, during the battery charge and discharge cycle, as the SC bond is homolytically split to generate fluorosulfonyl radicals, the fluorosulfonyl radicals are highly active and will capture oxygen atoms in the electrolyte solvent to generate lithium fluorosulfonate. Lithium fluorosulfonate has a simple molecular structure, high stability, and high conductivity, thereby improving the high-temperature performance of lithium-ion batteries.

[0048] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A non-aqueous electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, characterized in that: The additive includes a compound A shown in structural formula I: And, compound B shown in structural formula II: Wherein, R1 is selected from halogen or alkylphenyl, and R2, R3, R4, R5, and R6 are each independently selected from hydrogen, halogen, cyano, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted alkynyl, substituted or unsubstituted alkoxy, or substituted or unsubstituted sulfonyl.

2. The nonaqueous electrolyte according to claim 1, characterized in that R1 is selected from halogen or methylphenyl, and R2, R3, R4, R5, and R6 are each independently selected from hydrogen, halogen, cyano, substituted or unsubstituted C1~C10 alkyl, substituted or unsubstituted C2~C10 alkenyl, substituted or unsubstituted C2~C10 alkynyl, substituted or unsubstituted C1~C10 alkoxy, and substituted or unsubstituted C1~C10 sulfonyl.

3. The non-aqueous electrolyte according to claim 1, characterized in that The compound B is selected from at least one of compounds 1 to 11: 。 4. The non-aqueous electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the non-aqueous electrolyte is 0.05-5%, and the mass percentage of the compound B in the non-aqueous electrolyte is 0.05-5%.

5. The non-aqueous electrolyte according to claim 1, characterized in that The lithium salt is selected from at least one of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisoxalatoborate, lithium difluorophosphate, lithium fluorosulfonate, lithium difluorooxalatoborate, lithium lower aliphatic carboxylate, lithium difluorobisoxalatophosphate and lithium bisfluorosulfonyl imide.

6. The non-aqueous electrolyte according to claim 5, wherein the mass percentage of the lithium salt in the non-aqueous electrolyte is 5-25%.

7. The non-aqueous electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is selected from at least one of carboxylic acid esters, carbonate esters and ether compounds.

8. The non-aqueous electrolyte according to claim 1, characterized in that The invention also comprises an auxiliary agent, which is selected from at least one of fluoroethylene carbonate, vinylene carbonate, 1,3-propane sultone, vinyl sulfate, 1,3-propylene glycol cyclic sulfate, 1,4-butane sultone, triallyl phosphate and succinic anhydride.

9. A lithium ion battery comprising a positive electrode material and a negative electrode material, characterized in that: It also includes the non-aqueous electrolyte according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 1, characterized in that: The positive electrode material is selected from lithium cobalt oxide.

Citation Information

Patent Citations

  • Electrolyte for lithium-ion battery and lithium-ion battery

    CN105742707A

  • Battery monomer, preparation method thereof, battery comprising battery monomer, and power utilization device

    CN117254114A

  • Electrolyte additive composition containing novel lithium salt and application thereof

    CN119340477A

  • Non-aqueous electrolyte and lithium ion battery thereof

    CN119419357A

  • (2-cyanoethyl) phosphonium salt-based electrolyte composition, and battery comprising same

    WO2024105128A1